Some Indicators of Antibody-Independent Effector Mechanisms in Latent Sero-Resistant Forms of Syphilis - Olesya A.Vasileva³; Elena V. Chekrygina¹; Milana M. Minasyan¹; Alexei V. Odinets, PhD²; Azret Kh. Kaziev, PhD, ScD¹ (International Journal of Biomedicine, 2012)
Currently, there is an alarming increase in the syphilis rates accompanied by a proportional rise in the incidence of latent forms of the disease among the population of several countries. Latent syphilis considerably delays timely detection, diagnosis and, therefore, the specific early treatment of patients. In 2007, the proportion of latent forms of syphilis in the Russian Federation amounted to 49.7% of all reported syphilis cases [6]. Importantly, it is very important to note latent syphilis was found in each of the 4 cases of HIV-infected patients. The absence of clinical manifestations in patients with this type of syphilis is of great scientific and practical interest, and only serological examination is seen to contribute to the diagnosis of this disease. The properties of the Treponema pallidum (TP) and the state of immunity in the infected person are well known to be the main factors influencing the development of the pathology. However, studying the properties of the causative agent of syphilis is quite impossible because modern strains of TP are absent. In this connection, the relevance of studying the characteristics of protective mechanisms in the latent forms of syphilis is obvious. In our study, we investigated the amount of T-lymphocytes and their subpopulations, which are CD2, CD3, CD4, CD8, CD16, CD19 and CD25. The study identified a significant deficiency of CD4+ and suppressive/cytotoxic T cells, as well as significantly low levels of CD25, which is important in stimulating the proliferation of T and NK cells.